Peanut Smut : from an emerging disease to an actual threat to Argentine Peanut production - Rago, Alejandro Mario (2017)
The center of origin of peanut is located in South America, specifically in southeastern Bolivia and northwestern Argentina, where its parental species are found in wild habits. Even though Argentina is only the seventh largest producer of peanut in the world (2% of global production), it is the leading exporter of edible grain and crushed (e.g., flour, butter, and oil) peanut products worldwide. Peanut production was moved to more southern areas of Cordoba in the early 1990s to avoid the consequences of production issues in the northern region. During this migration process, a new disease emerged in commercial plots: peanut smut caused by Thecaphora frezii. Peanut smut was first detected in the northern peanut producing areas in Córdoba Province, and then established on the central region where the main grain processing industries are located. Currently, the prevalence is 100% in Argentinian peanut area. This finding showed evidence that pathogens could also migrate along with peanut production activities and contaminate soil of new production areas